Who rules where over whom when the fighting stops? Explaining state and secessionist post-war strategies for controlling territory and people - Barker, N (2020)
This study explains the causes of state and secessionist post-war strategies for controlling territory and people. The objective is to improve our understanding of how secessionist wars end and what happens next by providing new insights into two important cases and using these cases to build a more general framework, thereby contributing to a growing research agenda on war to peace transitions and post-war environments. The study uses a theory building research strategy with two case studies – the Georgia-Abkhazia conflict (covering the period 1994-2006) and the Serbia-Kosovo conflict (1999-2008) – to develop an empirically-grounded theoretical framework. The resulting framework does four things. First, it conceptualises strategies in terms of the constitutive features of territorial and demographic control (territorial and demographic control strategies, the outcome of interest). Second, it theorises states’ and secessionists’ post-war objectives in terms of a cleavage of reincorporation versus full separation which is broken down into objectives about de facto control and reflect the constraints of a post-war environment (constrained objectives, the main explanatory factor). Third, it identifies territorial and demographic features of post-war environments that actors use to translate objectives into strategies (links and levers). Fourth, it provides an argument about how the parts fit together. Objectives explain strategies, mediated by the constraints and opportunities of the environment: demographic and territorial control strategies are explained in terms of the actors’ constrained objectives, and the links and levers which are used to translate objectives into strategies. The framework provides expectations about which control strategies are associated with particular constrained objectives (the observable implications of the framework), and through the theory building case studies and additional ‘shadow cases’, I provide evidence from seven post-war environments in the Caucasus and the Balkans in support of my argument, drawing on extensive empirical research from multiple sources, including fieldwork and archival research.